Wireless-controlled, self-powered, and patterned information encryption display system based on flexible electroluminescence devices. (November 2022) - Xia, Yifan; Zhu, Yan; Yang, Biao; Guo, Wenyu; Han, Shilei; Wang, Xin
Abstract: Information encryption is significantly important for information security, national public safety, and social business, which still face severe challenges of large-scale stimulus decryption equipment, information leakage, and product forgery. Herein, a wireless-controlled, self-powered, and patterned information encryption display system (IEDS) based on flexible electroluminescence (EL) device is developed, in which the EL device based on quick response (QR)/Morse-coded silver electrodes can be directly driven by a wearable triboelectric nanogenerator (W-TENG) to demonstrate programmed pixel-based dynamic EL emission for wireless-controlled information encryption. Moreover, the silver electrodes fabricated by inkjet printing for the EL device demonstrate high conductivity of 1.6 Ω/ sq and excellent flexibility. A wireless control module operated by a smartphone is employed to switch on or off the connection of the W-TENG with the EL device to achieve pixel-based dynamic EL emission for the IEDS, which would provide a novel insight and strategy for implementing advanced information encryption technology. Graphical Abstract: Wireless-controlled, self-powered, and patterned IEDS based on QR/Morse-coded-patterned EL device can be driven by W-TENG to achieve information encryption and information storage through dynamic emission display of EL device. Consumers would receive a message by scanning the QR/Morse-coded EL emission pattern with a smartphone to identify authenticity of the goods. ga1 Highlight: A wireless-controlled, self-powered, and patterned information encryption display system is developed based on EL device. The flexible patterned EL device driven by TENG can maintain uniform and stable light emission at various bending angles. The encrypted information can be dynamically displayed in IEDS by wireless communication with a smartphone. The QR/Morse-coded IEDS demonstrates the capability to identify authenticity of the goods based on dynamic EL emission.